Peer tutoring programmes: Comprehensive training and generic competences from the experience of tutors in a Chilean university - Camila Véliz; Oscar Navarrete (Tuning Journal for Higher Education)
Like other countries, higher education in Chile still has important socio-economic gaps to be addressed. As part of the strategies to attend this challenge, peer tutoring programmes have developed considerably in recent years. Much of the research on peer tutoring in higher education has focused primarily on the impact on the students being tutored, and only a small part of that research has focused on the benefits or contributions to the student-tutors themselves. Based on a case study of peer tutoring programmes in a Chilean university, the experience of tutor participation and its relationship to comprehensive training competences is collected from interviews. The information was analysed based on the following categories: understanding of comprehensive training, perceptions of their role, motivation and learning from their experience. The main results aim to highlight the relationship between generic interpersonal, instrumental and systemic competences and their link to comprehensive training. It is concluded that interpersonal competences amount to the main benefit self-perceived by the tutors, where self motivation, learning orientation, planning strategies and strengthening their autonomy and identity emerged as the main competences developed. While both students and tutors benefit from peer tutoring, tutors are a key participant in the integral formation, strengthening their social commitment.